Nucleus Morphometry in Cultured Epithelial Cells Correlates with Phenotype. (22nd June 2016) - Khan, Ayyad Z.; Utheim, Tor P.; Jackson, Catherine J.; Reppe, Sjur; Lyberg, Torstein; Eidet, Jon R.
Abstract: Phenotype of cultured ocular epithelial transplants has been shown to affect clinical success rates following transplantation to the cornea. The purpose of this study was to evaluate the relationship between cell nucleus morphometry and phenotype in three types of cultured epithelial cells. This study provides knowledge for the development of a non-invasive method of determining the phenotype of cultured epithelium before transplantation. Cultured human conjunctival epithelial cells (HCjE), human epidermal keratinocytes (HEK), and human retinal pigment epithelial cells (HRPE) were analyzed by quantitative immunofluorescence. Assessments of nucleus morphometry and nucleus-to-cytoplasm ratio (N/C ratio) were performed using ImageJ. Spearman's correlation coefficient was employed for statistical analysis. Levels of the proliferation marker PCNA in HCjE, HEK, and HRPE correlated positively with nuclear area. Nuclear area correlated significantly with levels of the undifferentiated cell marker ABCG2 in HCjE. Bmi1 levels, but not p63 α levels, correlated significantly with nuclear area in HEK. The N/C ratio did not correlate significantly with any of the immunomarkers in HCjE (ABCG2, CK7, and PCNA) and HRPE (PCNA). In HEK, however, the N/C ratio was negatively correlated with levels of the undifferentiated cell marker CK14 and positively correlated with Bmi1 expression. The size of the nuclear area correlated positively with proliferation markers in all three epithelia. Morphometric indicators of phenotype in cultured epithelia can be identified using ImageJ. Conversely, the N/C ratio did not show a uniform relationship with phenotype in HCjE, HEK, or HRPE. N/C ratio therefore, may not be a useful morphometric marker for in vitro assessment of phenotype in these three epithelia.